Assessing the Needs of Carers of People with Mental Illness: Lessons from a Collaborative Study. Issue 4 (7th August 2016) - Watts, Lynelle; Hodgson, David
Abstract : This paper is concerned with improving assessment practices with people who are carers of people with mental illness. It is established that the well-being of carers is negatively impacted by the burden of their caring role, and that the needs of carers are often overlooked and poorly responded to by formal helping services. It is the purpose here to report on findings from the data provided by a subset of participants from a broader collaborative research project that developed and trialled a carer's assessment tool. The goal was to establish whether the tool was useful in practice for the purposes of assessment. This paper outlines key principles for practitioners and services to consider in their assessment practices with carers. These include an assessment process that allows carers to focus on their own feelings independent of the person they may be caring for; the importance of developing a feeling of solidarity with other carers while validating their caring experience; a comprehensive and holistic assessment process; and, opportunities to prioritise in a collaborative manner what might be an overwhelming number of areas of need or concern.